A Walk through the City with John Chrysostom: Psychogeography, Virtue and the Urban Ascetic in the Homilies On Ephesians 15 and On Hebrews 28 - De Wet, Chris L. (Neotestamentica, 2020)
This article combines two methodological and conceptual trajectories—the first being the rise of the Christian polis and the centrality of Christian discourse, and the spatial turn in early Christian studies; the second being psychogeography. Michel De Certeau’s exploration of the notion of walking in the city has been most influential in conceptualising psychogeography, and also informs the approach in this article. The study examines how one late antique Christian homilist, namely John Chrysostom (ca. 349-407 CE), negotiates, psychogeographically, with urban spaces in relation to his views on virtue formation, focusing on homily 15 On Ephesians and homily 28 On Hebrews. In many of Chrysostom’s homilies one finds sporadic ekphrases of city life, or rather, scenes and exhibitions of urban spatial practices. In psychogeographical terms, Chrysostom’s wanderings blossom as a form of dérive— strategic technologies of voyeuristic ambulation through necessitated yet varied ambiences, leading out to an archaic détournement, in which the complex quotidian pratiques of the vice-laden city are exposed unaesthetically and used against itself. Thus, such ekphrases are strategic in that they serve as illustrative, practical examples of the dynamics and problems of virtue formation in the urban setting. In the style of a visionary urban wanderer, Chrysostom takes his audience on seemingly random, yet very strategic, strolls through the city and then pauses at some spatial practices for psychopedagogical reasons.